The Fit Between the UK Environmental Information Regulations and the Freedom of Information Act - Colin Pelton; Mark Thorley (International Journal of Digital Curation, 2008)
The Natural Environment Research Council (NERC) is one of seven UK Research Councils. It delivers independent research, survey, training and knowledge transfer in the environmental sciences. All the UK Research Councils are public bodies falling under the Freedom of Information Act 2000 and the Environmental Information Regulations 2004. This open access legislation came into force on January 1, 2005 and since then the authors have built up substantial experience in managing NERC’s data and information under both the Act and the Regulations. This article aims to explain how to manage the, often blurred, boundary between these two pieces of legislation, and the overlap between data management and the legislation.